Diseño de Assesment Center como herramienta de evaluación de candidatos dentro del proceso de selección de personal de la empresa Abrus Ingeniería y Medio Ambiente Cía. Ltda. - Cevallos Torres, Frank Andrés (2014)
The assessment center design as a tool for evaluating candidates in the selection process of the Abrus Engineering and Environmental Company Cia. Ltda is born as a business necessity, once the analysis of the indicators of both turnover and effectiveness of the selection process were realized, which are negative. In the first place, it was identified that in order to design the tool was necessary to restructure and create some basic inputs starting with the selection process change, the creation of organizational and specific skills by position in the company that were summarized in two dictionaries, one of competencies, and the other one of behaviors; both dictionaries were adapted from Martha Alles’s dictionaries, the update for manual functions was performed by changing the description of the activities and the hard profile, to a skills profile.